Influence of Peroxisome Proliferator-Activated Receptor (PPAR)-gamma Coactivator (PGC)-1 alpha gene rs8192678 polymorphism by gender on different health-related parameters in healthy young adults - Montes-de-Oca-García, Adrián; Corral-Pérez, Juan; Velázquez-Díaz, Daniel; Perez-Bey, Alejandro; Rebollo-Ramos, María; Marín-Galindo, Alberto; Gómez-Gallego, Félix; Calderon-Dominguez, Maria; Casals, Cristina; Ponce-González, Jesús G. (Frontiers in Physiology, 2022)
This study aimed to analyze the influence of the peroxisome proliferator-activated receptor (PPAR)-gamma coactivator (PGC)-1 alpha (PPARGC1A) gene rs8192678 C>T polymorphism on different health-related parameters in male and female young adults. The PPARGC1A gene rs8192678 polymorphism was ascertained by polymerase chain reaction in 74 healthy adults (28 women; 22.72±4.40 years) from Andalusia (Spain). Health-related variables included cardiometabolic risk, anthropometry and body composition, biochemical parameters, insulin sensitivity (QUICKI and HOMA-IR indexes), blood pressure (BP) at rest and after exercise, diet, basal metabolism, physical activity, maximal fat oxidation, and cardiorespiratory fitness. Our results showed differences by PPARGC1A gene rs8192678 C>T polymorphism in body mass (p=0.002), body mass index (p=0.024), lean body mass (p=0.024), body fat (p=0.032), waist circumference (p=0.020), and BP recovery ratio (p<0.001). The recessive model (CC vs. CT/TT) showed similar results but also with differences in basal metabolism (p=0.045) and total energy expenditure (p=0.024). A genotype*sex interaction was found in the QUICKI index (p=0.016), with differences between CC and CT/TT in men (p=0.049) and between men and women inside the CT/TT group (p=0.049). Thus, the PPARGC1A gene rs8192678 C>T polymorphism is associated with body composition, basal metabolism, total energy expenditure, and BP recovery, where the CC genotype confers a protective effect. Moreover, our study highlighted sexual dimorphism in the influence of PPARGC1A gene rs8192678 C>T polymorphism on the QUICKI index.